ANALISIS HISTORIS STRATEGI PERANG MONGOL DALAM PENAKLUKAN IRIAN BARAT OLEH BANGSA EURASIA - Putra, Doly Andhika; Ghazalie, Ghazalie (Universitas Negeri Malang, 2024)
A HISTORICAL ANALYSIS OF MONGOL WARFARE STRATEGY IN THE EURASIAN CONQUEST OF THE WEST IRIAN WARThis article explores the warfare strategies employed by the Mongols in their quest to conquer Eurasia. In the era of leaders like Genghis Khan and his successors, the Mongols expanded their territory to reach most of the Eurasian continent. This success was due to careful military strategy, diplomacy, and other effective approaches. This article analyzes these strategies to provide a clear picture of how this nomadic nation became the dominant power in the ancient world. The research methodology utilizes an in-depth historical approach with four main steps: source collection, source criticism, data interpretation, and historical writing. The article provides valuable insights into how the Mongols formulated and executed their warfare strategy through this process. The research shows that Mongol success was not only due to military might but also to adaptability, diplomacy, and knowledge of the enemy and the battlefield. The article's conclusion emphasizes the importance of understanding the complexity of the strategies and tactics employed by the Mongols in a historical and military context.Artikel ini mendalami strategi peperangan yang diterapkan oleh bangsa Mongol dalam upaya mereka menaklukkan Eurasia. Di era kepemimpinan seperti Genghis Khan dan penerusnya, Mongol berhasil memperluas wilayahnya hingga mencapai sebagian besar benua Eurasia. Keberhasilan ini bukan tanpa alasan, melainkan berkat strategi militer yang cermat, diplomasi, dan pendekatan lain yang efektif. Dalam artikel ini, strategi tersebut dianalisis untuk memberikan gambaran yang jelas tentang bagaimana bangsa nomaden ini dapat menjadi kekuatan dominan di dunia kuno. Metodologi penelitian ini menggunakan pendekatan historis yang mendalam dengan empat langkah utama: pengumpulan sumber, kritik sumber, penafsiran data, dan penulisan sejarah. Melalui proses ini, artikel memberikan wawasan berharga tentang bagaimana bangsa Mongol memformulasi dan melaksanakan strategi peperangan mereka. Penelitian ini menunjukkan bahwa keberhasilan Mongol bukan hanya berkat kekuatan militer semata, tetapi juga kemampuan adaptasi, diplomasi, dan pengetahuan tentang musuh serta medan perang. Kesimpulan dari artikel ini menekankan pentingnya memahami kompleksitas strategi dan taktik yang diterapkan oleh Mongol dalam konteks sejarah dan militer.